2021
DOI: 10.1101/2021.02.26.21252487
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization and mitigation of aerosols and splatters from ultrasonic scalers

Abstract: Background: Dental procedures often produce aerosols and splatter which have the potential to transmit pathogens such as SARS-CoV-2. The existing literature is limited. Methods: Aerosols and splatter were generated from an ultrasonic scaling procedure on a dental mannequin and characterized by two optical imaging methods – digital inline holography (DIH) and laser sheet imaging (LSI). Capture efficiencies of various aerosol mitigation devices were evaluated and compared. Results: The ultrasonic scaling proce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…5 17 EOVA is more effective when located 14 mm from the working zone rather than 18 mm. 21 However, studies on the effectiveness of HVE and EOVA are still limited and further studies on the design, power, and recommended instructions for using these devices are still needed.…”
Section: Discussionmentioning
confidence: 99%
“…5 17 EOVA is more effective when located 14 mm from the working zone rather than 18 mm. 21 However, studies on the effectiveness of HVE and EOVA are still limited and further studies on the design, power, and recommended instructions for using these devices are still needed.…”
Section: Discussionmentioning
confidence: 99%
“…10. Note that Ou et al (2021) studied the splatter produced from an ultrasonic scaler using a similar (7)…”
Section: Case 1: Plane P 1 Cavitron At 0 °Asmentioning
confidence: 99%
“…They utilized an approach called laser sheet imaging (LSI) to capture the far field splatter in a 14 cm × 14 cm field of view. They also used an ultrasonic scaler in conjunction with different evacuation methods (Ou et al 2021) where they found the majority of the splatter produced from a scaling procedure on tooth #25 or #24 was less than 2 m/s (Ou et al 2021).…”
Section: Case 1: Plane P 1 Cavitron At 0 °Asmentioning
confidence: 99%
See 2 more Smart Citations